1970
DOI: 10.1002/qj.49709640907
|View full text |Cite
|
Sign up to set email alerts
|

Reflection coefficient of natural vegetation, crops and urban surfaces in Nigeria

Abstract: SUMMARYReflection coefficients measured over a wide variety of natural and agricultural vegetation surfaces in Nigeria (lat. 4 ' 40' to 13" 30") were between 0.05, to 0.25,; and were inversely related to the vegetation height. Considerable seasonal differences were found with unexpected low values of reflectivity during the harmattan haze in the dry season. Possible reasons for these seasonal differences are discussed. The weighted mean annual reflection coefficient for Nigeria was calculated to be 0.178. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

1972
1972
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 16 publications
5
22
1
Order By: Relevance
“…Results there have ranged between 0.1225 (Shuttleworth et al, 1984) and 0.134 (Culf et al, 1995). Measurements taken elsewhere are in general agreement with Amazonian values, with 0.12 found in Nigeria (Oguntoyinbo, 1970) and 0.13 in Thailand (Pinker, 1982). Albedo of deforested tropical surfaces is more variable, dependent on the replacement land cover.…”
Section: Albedo Of Tropical Land Surfaces: Previous Researchsupporting
confidence: 73%
See 1 more Smart Citation
“…Results there have ranged between 0.1225 (Shuttleworth et al, 1984) and 0.134 (Culf et al, 1995). Measurements taken elsewhere are in general agreement with Amazonian values, with 0.12 found in Nigeria (Oguntoyinbo, 1970) and 0.13 in Thailand (Pinker, 1982). Albedo of deforested tropical surfaces is more variable, dependent on the replacement land cover.…”
Section: Albedo Of Tropical Land Surfaces: Previous Researchsupporting
confidence: 73%
“…Bastable et al (1993), Fisch et al (1994), and Culf et al (1995) obtained albedo for Amazonian pasture ranging from 0.163 to 0.190. Oguntoyinbo (1970) found albedo ranged from 0.15 to 0.21 for nonforested locations in Nigeria. Pinker (1982) measured a mean albedo of 0.150 for tall grass in a forest clearing in Thailand.…”
Section: Albedo Of Tropical Land Surfaces: Previous Researchmentioning
confidence: 95%
“…RR followed RG, representing 14%-19% (surface albedo, α0) of its values, despite having higher spatial variations when compared to RG, and according to moisture conditions and ecosystem characteristics. Monteith and Unsworth [38] [39][40][41]. These similarities confirm the validity of Equation (1) applied to MODIS images for the Pantanal ecosystems.…”
Section: Large-scale Radiation Balancesupporting
confidence: 69%
“…Others are increased rainfall that is accompanied by devastating storms and urban floods. Viewing these enormous problems and the earlier call by [1], some urban climate studies in Nigeria have examined the urban influence on components of climates characteristics namely: global radiation [5] [26], net radiation [26], temperature and albedo [4] [5] [27]. These studies showed that while net radiation and albedo values in urban are lower than the values measured in rural area, temperature is higher in urban areas than in rural areas.…”
Section: Introductionmentioning
confidence: 99%